The effects of contingent relationship magnitude between pay and performance on social loafing behaviors - Choi, Insub; Lee, Kyehoon; Oah, Shezeen (Korean Journal of Industrial and Organizational Psychology, 2013)
The main purpose of this study was to compare the effects of contingent relationship magnitude between pay and performance on social loafing behaviors and perception of the distributive justice. Sixty-four college students were applied in an ABC/ACB counter-balancing mixed factorial design(A: the high contingent relationship magnitude between pay and performance on individual performance, B: the high contingent relationship magnitude between pay and performance on team performance, C: the low contingent relationship magnitude between pay and performance on team performance), each participant attended 12 sessions in total. For this study, a brainstorming task was developed. The dependent variable was the sum of total idea frequency in the brainstorming task and the perception of the distributive justice. Analyses showed that each condition of contingent relationship magnitude between pay and performance had effectiveness in team idea frequency and perceived distributive justice. Result indicated that teamwork was better than individual work on performance. Also, the result suggested that social loafing behaviors or perception of the distributive justice could be effected depend upon the extent to which how the contingent relationship magnitude between pay and performance on team performance.